Associations of sugar-related food parenting practices and parental feeding styles with prospective dietary behavior of children and adolescents: a systematic review of the literature from 2017 to 2023 - Hübner, Hannah Leonike; Bartelmeß, Tina (Frontiers in Public Health, 2024)
High consumption of sugar-rich foods and beverages has been associated with increased overweight and obesity in children and adolescents. Dietary behavior is influenced by learned mechanisms that originate in childhood and is associated with food parenting practices (FPP) and parental feeding styles (PFS). This systematic review aimed to narratively synthesize FPP and PFS concerning sugar-rich foods and beverages and their associations with the prospective dietary behavior of children and adolescents to derive evidence-based recommendations for health professionals and parents to promote healthy behaviors. A systematic literature search was conducted using PubMed and Web of Science databases covering the publication years 2017-2023. The results were narratively synthesized, and exposure-outcome matrices were used for visual representation. The review included 15 peer-reviewed studies from different geographical regions that investigated FPP or PFS regarding the handling of sugar-rich foods and beverages in children's diets and reported the associations with the prospective dietary behavior of children and adolescents. The findings indicate that highly controlling parental practices were associated with the development of unhealthy eating behaviors and preferences for sugar-rich foods and beverages over time. Conversely, parental practices that emphasized structure and balance in dietary choices yielded more positive long-term outcomes, associated with reduced preferences for sugar-rich foods and drinks. The results underscore the significance of fostering a healthy home environment and active parental role modeling in promoting healthier dietary behaviors among children and adolescents.